Motivasi Kerelawanan Lansia: Dalam Persfektif Islam - Rifki Syarani Fachry; Sari Viciawati Machdum (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2022)
The involvement of the elderly in religious activities cannot be separated from their volunteer motivation. The purpose of this study is to analyze the Islamic view of volunteer motivation. The research method used in this study is literature review, the type of literature review in this study is an integrative review. The results of the literature review show that volunteering is an action taken by someone because the person feels religiously responsible to volunteer and is morally motivated to carry out volunteer activities. The concept of volunteerism in Islam illustrates how volunteerism in its various forms is an inseparable part of the dimensions of tradition and worship in Islam.